Cancellation of the Cardiac Catheterization Lab After Activation for ST-Segment–Elevation Myocardial Infarction: Frequency, Etiology, and Clinical Outcomes. Issue 8 (August 2018) - Lange, David C.; Conte, Stanley; Pappas-Block, Effie; Hildebrandt, David; Nakamura, Mamoo; Makkar, Raj; Kar, Saibal; Torbati, Sam; Geiderman, Joel; McNeil, Nathan; Cercek, Bojan; Tabak, Steven W.; et al.
Abstract : Background: Prehospital ECG-based cardiac catheterization laboratory (CCL) activation for ST-segment–elevation myocardial infarction reduces door-to-balloon times, but CCL cancellations (CCL X ) remain a challenging problem. We examined the reasons for CCL X, clinical characteristics, and outcomes of patients presenting as ST-segment–elevation myocardial infarction activations who receive emergent coronary angiography (EA) compared with CCL X . Methods and Results: We reviewed all consecutive CCL activations between January 1, 2012, and December 31, 2014 (n=1332). Data were analyzed comparing 2 groups stratified as EA (n=466) versus CCL X (n=866; 65%). Reasons for CCL X included bundle branch block (21%), poor-quality prehospital ECG (18%), non–ST-segment–elevation myocardial infarction ST changes (18%), repolarization abnormality (13%), and arrhythmia (8%). A multivariate logistic regression model using age, peak troponin, and initial ECG findings had a high discriminatory value for determining EA versus CCL X (C statistic, 0.985). CCL X subjects were older and more likely to be women, have prior coronary artery bypass grafting, or a paced rhythm ( P <0.0001 for all). All-cause mortality did not differ between groups at 1 year or during the study period (mean follow-up, 2.186±1.167 years; 15.8% EA versus 16.2% CCL X ; P =0.9377). Cardiac death was higher in the EA group (11.8% versus 3.0%; P <0.0001). After adjusting for clinical variables associated with survival, CCL X was associated with an increased risk for all-cause mortality during the study period (hazard ratio, 1.82; 95% CI, 1.28–2.59; P =0.0009). Conclusions: In this study, prehospital ECG without overreading or transmission lead to frequent CCL X . CCL X subjects differ with regard to age, sex, risk factors, and comorbidities. However, CCL X patients represent a high-risk population, with frequently positive cardiac enzymes and similar short- and long-term mortality compared with EA. Further studies are needed to determine how quality improvement initiatives can lower the rates of CCL X and influence clinical outcomes.